Health-related behaviors and associated factors among swimming pool users in Kombolcha Town, Northeastern Ethiopia - Tarikuwa Natnael (Frontiers Media S.A., 2022)
ObjectiveUnhealthy behaviors during swimming exposes at risk of recreational water-associated diseases. The swimming pool users are the high-risk group for getting and transmitting the diseases. Thus, conducting a study on swimming pool users' health-related behaviors is crucial to prevent the transmission of recreational water-associated diseases.MethodsThis cross-sectional study was employed among 140 randomly selected swimming pool users from April 1st to 30th, 2021 in Kombolcha Town. Data were collected using an interviewer-administered questionnaire and an on-the-spot-observational checklist. The collected data were entered to EpiData version 4.6 and exported to SPSS version 25 for data cleaning and analysis. Determinants of health-related behaviors were identified by using a multivariable logistic regression model at a p-value < 0.05.ResultsThe overall good health-related behavior among swimming pool users was 41.4% (95% CI: 33.6-49.3). Out of the total 140 swimming pool users, 55% (95% CI: 46.4-62.9) had good knowledge about health risks during swimming. Good knowledge about health risks during swimming (AOR = 9.64; 95% CI: 3.14-29.61), educational status of college or above (AOR = 6.52; 95% CI: 1.76-24.10) and age being > 28 years (AOR = 6.49; 95% CI: 2.34-18) were factors significantly associated with good health-related behaviors.ConclusionThe finding of the study showed that the majority of the swimming pool users had poor health-related behaviors. Thus, Kombolcha Town Health Bureau and swimming pool managers should give attention to this population to enhance health-related behaviors through addressing the significant predictors.